Mucoromycota tannases: activity screening, production and enzyme purification - Kovács, Tamás; Kasziba, Zsófia Sára; Kovács, Anita; Vágvölgyi, Csaba; Papp, Tamás; Mondal, Keshab Chandra; Krisch, Judit; Takó, Miklós (Acta Biologica Szegediensis, 2025)
Tannases are industrial enzymes that catalyze the degradation of hydrolysable and complex tannins into gallic acid and glucose. While many filamentous fungi are known high-yield producers, members of Mucoromycota remain less studied regarding tannase production. This study screened Mucoromycota isolates for tannase production using plate tests with tannic acid as an enzyme production inducer. Isolates of Rhizomucor miehei, Mucor corticolus, Mucor lusitanicus, Rhizopus microsporus var. oligosporus, and Rhizopus oryzae exhibited tolerance to the inducer, with tannase production detected in most strains post-incubation. Tannic acid effectively induced tannase production under both submerged fermentation (SmF) and solid-state fermentation (SSF) conditions. In SSF, wheat bran as a substrate and Czapek-Dox solution as a moisturizing additive supported enzyme production. The highest tannase activity in SSF was observed in R. microsporus var. oligosporus and M. corticolus, while R. miehei excelled under SmF conditions. Tris buffer extraction followed by anion exchange chromatography yielded tannase-active protein fractions from M. corticolus. The isolated tannase exhibited optimal activity at 30 °C. These findings highlight Mucoromycota fungi as promising tannase producers for future research.